2018
DOI: 10.1099/jmm.0.000759
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the genome diversity and virulence of two clinical isolates of Burkholderia cenocepacia

Abstract: This study mapped existing genetic variations in B. cenocepacia associated with notorious outcomes in CF patients, and the data obtained provide comprehensive, genome-inferred insights and multifactorial examination of an important human pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Resistance genes were observed against meropenem, trimethoprim/sulfamethoxazole, levofloxacin, and cefepime, despite the susceptibility described according to the disk diffusion test (DDT), considered as multidrug-susceptible, corroborating previous studies that revealed no direct correlation of gene expression with phenotype [25].…”
Section: Discussionsupporting
confidence: 84%
“…Resistance genes were observed against meropenem, trimethoprim/sulfamethoxazole, levofloxacin, and cefepime, despite the susceptibility described according to the disk diffusion test (DDT), considered as multidrug-susceptible, corroborating previous studies that revealed no direct correlation of gene expression with phenotype [25].…”
Section: Discussionsupporting
confidence: 84%
“…3 and 5). Specifically, BCC08 and BCC05 should represent B. cenocepacia genomovars IIIA and IIIB, respectively [23,56,57]. The dDDH and Fig.…”
Section: Reclassification Of the Bcc Based On Species Tree And Dddh/animentioning
confidence: 99%
“…At present, with the advent of next-generation sequencing technologies, an increasing number of complete genome sequences of the bacteria in the BCC have been published [21][22][23][24]. This provides an ideal opportunity for re-examining the taxonomy of BCC by traditional molecular methods.…”
mentioning
confidence: 99%
“…Confirmation of HGT was performed by a combination of BLAST screening and largescale phylogenetic trees. BLAST screening was performed based on our previous study [42]. In brief, candidate sequences in B. glumae were compared against sequences in the NCBI (National Center for Biotechnology Information) reference genome using BLASTp [43] followed by extracting the sequences with highest similarity for further study.…”
Section: Horizontal Gene Transfer (Hgt) Analysismentioning
confidence: 99%
“…These sequences were aligned using MAFFT [45], and the conserved region of each alignment was trimmed using TrimAI [46] with stringent settings. Maximum likelihood and Bayesian phylogenies were generated based on our previous study [42].…”
Section: Horizontal Gene Transfer (Hgt) Analysismentioning
confidence: 99%